Beyond multiculturalism? Rethinking Japan's “tabunka-kyōsei” through Axel Honneth's theory of recognition - Ishimatsu, Hiroyuki (Frontiers in Sociology, 2025)
IntroductionIn Japan, the concept of tabunka-kyōsei (tabunka-kyōsei) has emerged in response to the growing number of foreign residents, yet its ideological background and policy implications remain insufficiently examined in international discourse. Unlike multiculturalism in Europe, Canada, and Australia, it has evolved under Japan's unique social conditions and remains conceptually distinct.MethodsThis study adopts a normative theoretical approach, analyzing tabunka-kyōsei through Axel Honneth's theory of recognition. Selected local initiatives are used illustratively to explore broader conceptual implications without empirical validation of specific cases.ResultsThe analysis traces the development of foreign resident policies in Japan, identifies the distinctive ideological and institutional features of tabunka-kyōsei, and compares them with Western multiculturalism. Differences include limited rights-based frameworks and an emphasis on exchange and mutual understanding over institutional recognition.DiscussionApplying Honneth's three-layered framework of love, law, and solidarity, the study argues that institutional recognition and social solidarity are central to evaluating Japan's multicultural practices beyond cultural tolerance. The findings contribute to normative debates on tabunka-kyōsei and offer insights for designing inclusive policies in contemporary Japan.